DETERMINANTS OF CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE: EMPIRICAL EVIDENCE FROM MINING COMPANIES IN INDONESIA (2020–2022) - Raisa Delvina; Trie Nadilla; Muhammad Syafril Nasution (Universitas Sultanah Nahrasiyah, 2025)
This study aims to determine the influence of profitability, liquidity and leverage on corporate social responsibility (CSR) disclosures (case studies of mining companies listed on the Indonesia Stock Exchange (IDX) for 2020-2022). This study employs a quantitative research approach. Secondary data are used as the data collection technique, while the sample is selected using purposive sampling. Data analysis is conducted using EViews version 12, as the study utilizes panel data. The stages of analysis include classical assumption tests and the estimation of panel data regression models, consisting of the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). Selection of data regression models panel with chow test, hausman and lagrange multiplier, panel data regression analysis using t test, F test and the coefficient of determination (R2). The results of this study indicate that from the results of selecting the panel data regression model selected REM, then 1) Profitability has a significant positive effect on CSR recognition in Mining Companies Registered on the Indonesia Stock Exchange (IDX) in 2020-2022. 2) Liquidity has a significant negative effect on CSR recognition at Mining Companies Listed on the Indonesia Stock Exchange (IDX) for 2020-2022. 3) Leverage has a significant negative effect on CSR recognition in Mining Companies Listed on the Indonesia Stock Exchange (IDX) for 2020-2022. 4) Profitability, liquidity and leverage have a jointly significant positive effect on the recognition of CSR in Mining Companies Listed on the Indonesia Stock Exchange (IDX) in 2020-2022